Preparation and properties of cordierite glass-ceramic as veneer porcelain for silicon nitride dental ceramics. Issue 13 (October 2022) - Jiang, Lei; Wang, Tong; Yin, Shuang; Luo, Tao; Fang, Xia; Yuan, Jun; Tang, Xuehua; Wang, Yang; Li, Quan; Yang, Jian
Abstract: To develop thermally matched veneer porcelain for silicon nitride as potential dental ceramics, cordierite glass-ceramics with TiO2 and ZrO2 as nucleating agents and CaCO3 as sintering aids were prepared by sintering method. The cordierite glass-ceramics prepared by sintering and crystallization at 1100 °C for 1 h show the best comprehensive properties and meet the ISO 6872:2015 with flexural strength of 95 MPa, fracture toughness of 1.56 MPa·m 1/2, Vickers hardness of 5.06 GPa, coefficient of thermal expansion of 2.99 × 10 −6 /°C and chemical solubility of 60 μg/cm 2, respectively, and no cytotoxicity. The chromaticity values L * , a * , b * were 93.84, − 0.18 and 7.10 respectively, which still needs to be slightly adjusted to fall into the range of natural tooth. Interface bonding of cordierite glass-ceramics/Si3 N4 ceramics was preliminarily explored by powder coating, sintering and shear strength tests, which exhibits a bonding strength up to 7.75 MPa and a hybrid mode of cohesive and adhesive failure.